An integrated study on the pyrolysis mecanism of peanut shell based on the kinetic analysis and solid/gas characterization. (June 2021) - Tao, Wenmei; Zhang, Peng; Yang, Xingwei; Li, Hao; Liu, Yi; Pan, Bo
Graphical abstract: Highlights: Released low-molecular weight gases were online detected by TG-MS. Pyrolytic reaction was elucidated by thermodynamics, kinetics, and product analysis. Pyrolytic reaction mechanisms were identified as order-based reactions. CO2 release caused the weak alkaline of the derived biochar. Abstract: An in-depth understanding of peanut shell pyrolysis reaction is essential for its efficient utilization. Detailed analysis of thermodynamics, kinetics, and reaction products can provide valuable information about pyrolysis reaction. In this work, pyrolytic reaction mechanism was elucidated with the analysis of thermogravimetric-mass spectrometry and the structural characterization of the derived biochar. The thermodynamic and kinetic parameters of three sub-stages were matched well in different model-free methods. The positive ΔH and ΔG values indicated that the pyrolysis reactions for three stages were endothermic and nonspontaneous. The reaction mechanism predicted by integral master-plots were F3 (f(α) = (1-α) 3 ), F1 (f(α) = (1-α), and F3 (f(α) = (1-α) 3 ) for the three sub-stages, respectively. The negative ΔS in the third stage was related to the reduced releasing of low-molecular weight gases and ordered graphite-like carbon structure. This study provides a prospective approach to understand the pyrolysis mechanism of biomass.